2017
DOI: 10.20506/rst.36.3.2725
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del nivel de conocimiento de la brucelosis bovina entre personas vinculadas a la cadena de producción bovina en la provincia de Manabí, Ecuador

Abstract: A cross-sectional study was conducted to determine the level of knowledge about brucellosis among livestock farmers and their families, veterinary personnel, food processors and other people involved in the cattle supply chain in the province of Manabí. A voluntary, open-ended survey of participants was conducted in seven cantons in Manabí province selected at random: Bolívar, Chone, El Carmen, Jama, Junín, Sucre and Tosagua. Of the 500 people who responded to the survey, only 30% said they knew the disease. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…On average, the knowledge score of farmers for brucellosis was only 19.6%, with little difference between migratory and dairy farms. This is essentially in line with a previous study [ 23 ], which found that 15% of farmers in Tajikistan knew about brucellosis. In contrast, only 2.6% of farmers in Sri Lanka [ 12 ] and 4.8% of farmers in India [ 24 ] were aware that brucellosis is a zoonotic disease.…”
Section: Discussionsupporting
confidence: 92%
“…On average, the knowledge score of farmers for brucellosis was only 19.6%, with little difference between migratory and dairy farms. This is essentially in line with a previous study [ 23 ], which found that 15% of farmers in Tajikistan knew about brucellosis. In contrast, only 2.6% of farmers in Sri Lanka [ 12 ] and 4.8% of farmers in India [ 24 ] were aware that brucellosis is a zoonotic disease.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the number of farmers who knew about brucellosis as a zoonotic disease is higher than the finding of [9] in India (4.8%) and [1] in Pakistan (3%). Majority of farmers in this study (87.5%) don't have infor-mation how brucellosis can be transmitted and higher than the findings of [11] in Tajikistan (15%), [8] in Ecuador (30%) and [12] in Ethiopia (48%). The finding of this study is in contradiction to the result of [7] in Senegal where none of the farmer knew about brucellosis.…”
Section: Farmers' Practices and Knowledgementioning
confidence: 59%
“…Numerous variables are believed to influence the degree of brucellosis awareness and understanding. Multiple meta-analyses show that the education of the participants is correlated with higher levels of awareness and knowledge regarding brucellosis [ 17 - 26 ]. Awareness and knowledge of brucellosis are positively connected with prior experience and the prevalence of brucellosis in animals [ 27 ].…”
Section: Discussionmentioning
confidence: 99%